Occupational skin diseases: actual state analysis of patient management pathways in 28 European countries. (June 2017) - Mahler, V.; Aalto‐Korte, K.; Alfonso, J.H.; Bakker, J.G.; Bauer, A.; Bensefa‐Colas, L.; Boman, A.; Bourke, J.; Bubaš, M.; Bulat, P.; Chaloupka, J.; Constandt, L.; et al.
Abstract: Background: Work‐related skin diseases (WSD) are caused or worsened by a professional activity. Occupational skin diseases (OSD) need to fulfil additional legal criteria which differ from country to country. OSD range amongst the five most frequently notified occupational diseases (musculoskeletal diseases, neurologic diseases, lung diseases, diseases of the sensory organs, skin diseases) in Europe. Objective: To retrieve information and compare the current state of national frameworks and pathways to manage patients with occupational skin disease with regard to prevention, diagnosis, treatment and rehabilitation in different European countries. Methods: A questionnaire‐based survey of the current situation regarding OSD patient management pathways was carried out with experts on occupational dermatology and/or occupational medicine from 28 European countries contributing to the European Cooperation in Science and Technology (COST) Action TD 1206 (StanDerm) (www.standerm.eu ). Results: Besides a national health service or a statutory health insurance, most European member states implemented a second insurance scheme specifically geared at occupational diseases [insurance against occupational risks (synonyms: insurance against work accidents and occupational injuries; statutory social accident insurance)]. Legal standards for the assessment of occupationally triggered diseases with a genetic background differ between different countries, however, in most European member states recognition as OSD is possible. In one‐third of the countries UV light‐induced tumours can be recognized as OSD under specific conditions. Conclusion: OSD definitions vary between European countries and are not directly comparable, which hampers comparisons between statistics collected in different countries. Awareness of this fact and further efforts for standardization are necessary.